Shubnikov-de Haas oscillations in layered conductors with stacking faults: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Gvozdikov, V. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The Shubnikov-de Haas (SdH) oscillations of the in-plane conductivity of layered 2D electron gas is calculated. It is shown that layer stacking faults, magnetoimpurity bound states, and electron scattering modulate the SdH oscillations via the specific factors which bear the structural information. At zero temperature the 2D SdH oscillations are strongly nonsinusoidal in shape and related by simple equation to the derivative of the de Haas-van Alphen magnetization oscillations with respect to the magnetic field.